Processo de (re) inserção educacional do adolescente em cumprimento de medidas socioeducativas de Meio Aberto no município de Telêmaco Borba - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The present research focuses on socio-education as a public policy and the process of school (re)integration of adolescents undergoing socio-educational measures. The general objective is to understand how the process of educational (re)integration of adolescents under open-environment socio-educational measures takes place in the municipality of Telêmaco Borba, from the perspective of ensuring their fundamental rights. The specific objectives are: to discuss education as a fundamental right and its relevance to the social protection of adolescents undergoing socio-educational measures; to reflect on the role of social assistance policy and educational policy in the intersectoral implementation of socio-educational services from the perspective of ensuring the right to education; to analyze the role of the Specialized Social Assistance Reference Center (CREAS) and schools in the process of educational (re)integration as a social protection factor for adolescents undergoing socio-educational measures; and to reveal the main challenges in ensuring the right to education for adolescents under open-environment socio-educational measures in the municipality of Telêmaco Borba, from the perspective of social assistance and education professionals involved in the implementation of these measures. The research is qualitative, with a descriptive-exploratory approach, developed under the lens of historical-dialectical materialism. It comprises three stages: bibliographic, documentary, and field research, aiming to understand the research object through its concrete reality in dialogue with the theoretical framework. The study is based on authors from the fields of legal, social, and educational sciences, highlighting its interdisciplinary nature. The data collection procedures include documentary research based on the Individual Care Plans (PIA) of adolescents under open-environment socio-educational measures, focusing on the challenges and contradictions surrounding their school (re)integration process. Additionally, data is gathered through participant observation, field diaries, and semi- structured interviews with research subjects, namely, professionals from the multidisciplinary team at CREAS - Samuel Klabin and principals or pedagogues from state schools in Telêmaco Borba that receive adolescents undergoing socio- educational measures. The research findings highlight issues such as stigmatization, school dropout, the precariousness of pedagogical and psychosocial support services, and the reluctance of some education professionals to integrate these adolescents into the school environment. This study aims to contribute to unveiling the main challenges of the educational (re)integration process for these adolescents within the school context, fostering reflection and improving the open-environment socio-educational services in the municipality.
Keywords: proteção social; educação; direitos fundamentais; medidas socioeducativas; adolescentes em cumprimento de medidas socioeducativas.; social protection; education; fundamental rights; socio-educational measures; adolescents under socio-educational measures.; Ciências Sociais Aplicadas